Soil chemical properties as affected by plant derived ash to replace potassium fertilizer and its conversion value - John Bako Baon; Sugiyanto Sugiyanto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2011)
Potassium chloride (KCl) presently used as main source of K, tends to become more expensive, therefore, there is a need for a breakthrough in finding alternative materials to replace KCl. The aim of this paper is to present recent research on the use of plant derived ash to replace KCl fertilizer, especially in relation with soil chemical characteristics and its conversion value. Plant derived ash coming from palm sugar processing unit which use farm waste as main fuel was used in this experiment. Treatments investigated were no K2O application (control), applied with K2O in forms of both KCl and plant derived ash in dosages of 100, 200, 300, 400, 500 and 600 mg kg-1 air dry soil. The mixture of soil with those treatments were then incubated for one year. After incubation period, the soil in pots were divided into two parts, first part was added with 2g urea, while other part was added with 2 g SP 36. Both parts were incubated for two months. Results of this experiment showed that plant derived ash can be used to replaced KCl. To obtain similar soil K content, the amount of K2O in form of plant derived ash needed to be added or its conversion value is 1.44 times the amount of K2O in form of KCl. Use of plant derived ash also increased the content of soil Ca, available P, ratio of Ca/Mg and pH. Plant derived ash did not caused nitrogen loss. Key words: Potassium, fertilizer, plant derived ash, pH, soil.